From New Zion to Old Zion American Jewish Immigration and Settlement in Palestine, 1917-1939 - Glass, Joseph B. (Wayne State University Press, 2018)
American Aliyah (immigration to Palestine) began in the mid-nineteenth century fueled by the desire of American Jews to study Torah and by their wish to live and be buried in the Holy Land. His movement of people-men and women-increased between World War I and II, in direct contrast to European Jewry's desire to immigrate to the United States. Why would American Jews want to leave America, and what characterized their resettlement? From New Zion to Old Zion analyzes the migration of American Jews to Palestine between the two world wars and explores the contribution of these settlers to the building of Palestine. From New Zion to Old Zion draws upon international archival correspondence, newspapers, maps, photographs, interviews, and fieldwork to provide students and scholars of immigration and settlement processes, the Yishuv (Jewish community in Palestine), and America-Holy Land studies a well-researched portrait of Aliyah.